Ambient assisted living and enhanced living environments : principles, technologies and control - Dobre, Ciprian; ScienceDirect eBooks (Oxford, United Kingdom : Butterworth-Heinemann, 2017)
Ambient Assisted Living and Enhanced Living Environments: Principles, Technologies and Control separates the theoretical concepts concerning the design of such systems from their real-world implementations. For each important topic, the book bridges theory and practice, introducing the instruments needed by professionals in their activities. To this aim, topics are presented in a logical sequence, with the introduction of each topic motivated by the need to respond to claims and requirements from a wide range of AAL/ELE applications. The advantages and limitations of each model or technology are presented through concrete case studies for AAL/ELE systems. The book also presents up-to-date technological solutions to the main aspects regarding AAL/ELE systems and applications, a highly dynamic scientific domain that has gained much interest in the world of IT in the last decade. In addition, readers will find discussions on recent AAL/ELE technologies that were designed to solve some of the thorniest business problems that affect applications in areas such as health and medical supply, smart city and smart housing, Big Data and Internet of Things, and many more.
5.2.2 Closed Loop Healthcare as Typical AAL/ELE Application5.3 Communication Services to Support AAL/ELE Infrastructure; 5.4 Requirements of AAL/ELE Applications; Requirement 1 (SLA): AAL/ELE Need Dedicated Service Level Agreements (SLA) Between Actors and Network Service Provider; Requirement 2 (Costs): Low Upfront Infrastructure Investments for the User's Premises Equipment; Requirement 3 (Usability): Intuitive User Interfaces, Enhanced Usability Due to Self-* Capabilities and Easy Operation/Configuration of the Service.
Description based on online resource; title from title page (Safari, viewed December 21, 2016).
Includes bibliographical references and index.
Elsevier
Safari Books Online
Keywords: Ambient intelligence; Assistive computer technology; Ambient intelligence; Assistive computer technology; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Information Technology; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Electronic books